2004
DOI: 10.1080/10407780390244425
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Three-Dimensional Natural Convection of Water Cooled Inside a Cubic Enclosure

Abstract: Three-dimensional unsteady natural convection of cooling water inside a cubical cavity at Ra ¼ 10 5 is investigated. The finite-volume method with the SIMPLE algorithm is used to solve the nonlinear coupled continuity, momentum, and energy equations. All physical water properties-density, viscosity, thermal conductivity, and specific heat-are allowed to change with temperature. The numerical results for the 3-D geometry show that the side effects are relevant in fluid mechanics and in heat transfer, with large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The equations of conservation of mass, lineal momentum and discrete energy equations were discretized by using linear interpolation functions for the diffusion terms, while the convective terms were calculated by the fifth power law (Patankar 1980) . The SIMPLE algorithm was used to simultaneously solve the linear equations system using the line‐by‐line method (Moraga and Vega 2004). The tridiagonal matrix algorithm was used along with the Gauss–Seidel with successive under‐relaxation methods.…”
Section: Physical Situation and Mathematical Modelmentioning
confidence: 99%
“…The equations of conservation of mass, lineal momentum and discrete energy equations were discretized by using linear interpolation functions for the diffusion terms, while the convective terms were calculated by the fifth power law (Patankar 1980) . The SIMPLE algorithm was used to simultaneously solve the linear equations system using the line‐by‐line method (Moraga and Vega 2004). The tridiagonal matrix algorithm was used along with the Gauss–Seidel with successive under‐relaxation methods.…”
Section: Physical Situation and Mathematical Modelmentioning
confidence: 99%
“…A survey of the literature shows that correlations for natural convection from vertical and horizontal plates, vertical and horizontal cylinders, spheres, vertical channels, and elliptic cylinders have been reported for different thermal boundary conditions. Furthermore, numerical studies on heat transfer inside horizontal ducts, cavities, and enclosures have been reported by many authors for various boundary conditions [1][2][3][4][5][6][7][8][9][10][11], and natural convection in inclined rectangular enclosures have been studied by Rahman and Sharif [12] and by Sharif and Liu [13] for different aspect ratios and angles of inclination, respectively. However, limited numbers of analytical and numerical studies have been concerned with heat transfer from the external surface of rectangular ducts, which motivated the current study.…”
Section: Introductionmentioning
confidence: 99%
“…The representative works on steady-state [1][2][3][4][5][6][7][8][9][10] and transient [11][12][13][14][15][16][17][18][19][20] natural convection have all revealed that the density inversion phenomenon had great effect on the flow pattern, temperature field and heat transfer characteristic. Meanwhile, influences of internal heat generation [21] and magnetic field [22] on natural convection of water near its density maximum in a rectangular cavity were also investigated.…”
Section: Introductionmentioning
confidence: 99%